Synchronous improvement of piezoelectric property and temperature stability in PSN-PMN-PT ceramics by forming composites with ZnO. Issue 12 (September 2022) - Guo, Feifei; Dong, Shasha; Li, Kai; Wang, Junjun; Long, Wei; Fang, Pinyang; Li, Xiaojuan; Yang, Bin; Xi, Zengzhe
Abstract: Relaxor ferroelectric materials with high piezoelectric properties always suffer from low phase transition temperature, making them difficult to satisfy the demands for high-temperature environment applications. In this work, we proposed a composite approach to improve the piezoelectricity and temperature stability of PSN-PMN-PT ceramics at the same time. The ZnO nanoparticles as a second phase were introduced into the PSN-PMN-PT matrix to form composite ceramics. When the ZnO content reaches 5 mol%, the piezoelectric constant d 33 increases from 529 pC/N for pure PSN-PMN-PT ceramic to 590 pC/N. Meanwhile, the retained d 33 after annealing at 200 °C keeps 92% of the value before annealing, indicating the thermal depolarization behavior is suppressed by the composite method. The synchronous improvement of the d 33 and thermal depolarization behavior for PSN-PMN-PT/ZnO composite ceramics is related to the local electric field and stress field caused by the addition of ZnO particles. Our results pave a simple and effective way to develop next-generation PT-based relaxor ferroelectric ceramics.